Laos Tanpa Laut: Tantangan Akses Maritim di Bawah Unclos bagi Negara Landlocked - Diah Ayu Pramesti Makhadina (Jurnal Hukum Lex Generalis, 2026)
This study examines Laos’s maritime access as a landlocked country from the perspective of international law, specifically based on the United Nations Convention on the Law of the Sea (UNCLOS). Although UNCLOS guarantees the right of access to the sea and freedom of transit for landlocked countries, its implementation still faces various obstacles, including dependence on transit states, high logistics costs, complex administrative procedures, and the influence of political and economic factors in transit states. This study employs a normative legal research method with a legislative approach. The legal materials used consist of primary legal sources, such as international conventions and related legal instruments, as well as secondary legal sources, including books, journals and scholarly articles. The results of the study indicate that Laos’s geographical limitations impact the optimization of maritime access rights and the utilization of marine resources. Therefore, it is necessary to strengthen regional cooperation, optimize international legal instruments, and develop cross-border transportation infrastructure and connectivity to enhance maritime accessibility and support the sustainable economic development of Laos.